MANUSCRIPT XXXVII: Personal Narratives and Letters of Cook Islands 'Orometua Trained at Takamoa College. Issue 2 (3rd July 2022) - Rowan, Wendy
ABSTRACT: About 450 Cook Islander missionaries ( 'orometua ) and their wives worked in Melanesia and elsewhere in the Pacific between 1830 and 1926. Reproduced here are a selection of edited transcripts extracted mainly from the London Missionary Society's (LMS) Juvenile Missionary Magazine and its Missionary Magazine and Chronicle illustrating the experiences and attitudes of Cook Islander missionaries and their wives deployed by the LMS from 1853 to 1901. Testimonies of various kinds have been included from the following people: an unnamed teacher's wife on Maré; Teavae on Maré; Piri, his wife Maki and daughter Vaiola in Sāmoa and Papua; Ruatoka and his wife Tungane in Papua; Maka in Tokelau; and Isaako in Sydney bound for Papua. Taken together, they provide a valuable window onto this largely forgotten world.